Fokus 1950 : Norsk Billedkunst i etterkrigstiden - Arentz, Hans L.; Boym, Per Bjarne; Eckhoff, Audun; Gjessing, Steinar; Gunnarson, Ingebjorg; Hellandsjo, Karin; Michelet, Jon; Stromodden, Jarle; National Museum of Contemporary Art, Oslo (Oslo : Spartacus Forlag AS, 1998)
Winge, Sigurd ; Ekeland, Arne ; Enger, Erling ; Riis, Bendik ; Sparre, Victor ; Ryggen, Hannah ; Nasch, Rolf ; Meyer, Hans Jacob ; Haukeland, Arnold ; Rygh, Aase Texmon ; Gundersen, Gunnar S. ; Steen, Knut ; Orud, Kare ; Isern, Ramon ; Martinsen, Kare ; Hartmann, Alf Gabriel ; Aas, Alf-Jorgen ; Lie-Jorgensen, Thorbjorn ; Enger, Erling ; Bast, Ornulf ; Weidemann, Jakob ; Hoff, Tor ; Nesch, Rolf ; Heramb, Thore ; Rumohr, Knut ; Eikaas, Ludvig ; Tandberg, Odd ; Gundersen, Gunnar S. ; Bruland, Arne ; Haaland, Tore ; Alstad, Oddvar ; Weidemann, Jakob ; Kristiansen, Oddmund ; Ekeland, Arne ; Faaborg, Finn ; Blohm, Roy ; Ording, Doro ; Hagen, Else ; Aulie, Reidar ; Rian, Johs ; Ljosne, Halvdan ; Kongelf, Gudrun ; Andersen, Snorre ; Advocaat, Gunnvor ; Dal, Harald ; Bergman, Anna-Eva ; Bjaerke, Hakon ; Svarstad, Ernst Hakon ; Keiseraas, Karsten ; Sitter, Inger ; Tiller, Lars
Noors & Engels
Fokus 1950, National Museum of Contemporary Art, Oslo, 28. mars al 28 juni 1998
boek
Keywords: Noorwegen